(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to answer the following two questions: -What are the attitudes of chemistry teachers for the third intermediate grade towards applying differentiated education and their need to use it in teaching? Are there statistically significant differences at the 0.05 level in the use of differentiated instruction by third-grade chemistry teachers attributable to the gender difference? The researcher followed the descriptive-field approach to collect and analyze data to achieve the objectives of the study using the statistical program (SPSS). I designed an attitude scale as a tool for the study, which included (24) items and applied it to the study sample that was chosen intentionally, consisting of (140).A teacher and a school. The study population consisted of subject teachers in middle schools affiliated with the General Directorate of Education of Baghdad Governorate, Rusafa First and Second. Its apparent validity and reliability were verified by presenting it to a group of experts in the field of specialization. The results showed that there is no statistically significant difference between the arithmetic averages. For males and females in the gender variable of chemistry teachers’ attitudes towards implementing differentiated learning in middle schools. The research reached a set of conclusions, recommendations and proposals.